CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Expand $$(x+3)(x-3)$$


Solution

Using the identity is $$(x+y)(x-y)=x^{ 2 }-y^2$$.

GIven: $$(x+3)(x-3)$$,  we apply the above identity by taking $$a = 3$$ and $$b = -43$$
We get, $$(x+3)(x-3)={ \left( x \right)  }^{ 2 }-{ \left( 3 \right)  }^{ 2 }=x^{ 2 }-9$$

Hence, $$(x+3)(x-3)=x^{ 2 }-9$$.

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image